Cardiovascular risk profiling of long‐lived people shows peculiar associations with mortality compared with younger individuals. Issue 2 (16th December 2018) - Montesanto, Alberto; Pellegrino, Daniela; Geracitano, Silvana; La Russa, Daniele; Mari, Vincenzo; Garasto, Sabrina; Lattanzio, Fabrizia; Corsonello, Andrea; Passarino, Giuseppe
Abstract : Aim: Centenarians represent a biological model of successful aging because they escaped/postponed most invalidating age‐related diseases, such as cardiovascular diseases. The aim of the present study was to clarify whether a favorable cardiovascular risk profile increases the survival chances in long‐lived people. Methods: A total of 355 community‐dwelling nonagenarians and centenarians living in Southern Italy were recruited in the study. Patients were classified as at low and high cardiovascular risk on the basis of serum cholesterol, diabetes, hypertension and smoking status. The relationship between cardiovascular risk factors and 10‐year mortality was investigated by Cox regression analysis. Splines‐based hazard ratio curves were also estimated for total cholesterol, low‐density lipoprotein cholesterol, and systolic and diastolic blood pressure. Results: Low levels of selected cardiovascular risk factors usually associated with lower mortality in adults do not increase survival chances among oldest‐old individuals. In particular, after adjusting for age, sex, and cognitive, functional and nutritional status, serum cholesterol >200 mg/dL increased the survival chances during the follow‐up period (hazard ratio 0.742, 95% CI 0.572–0.963). Conclusions: The present results showed that in nonagenarians and centenarians, the clinical and prognostic meaning associated with traditional cardiovascular risk factors is very different from younger populations. Consequently, considering the increase of this population segment, further studies are required to confirm these results and to translate them into clinical practice/primary care.Geriatr Gerontol Int 2019; 19: 165–170 .